2018
DOI: 10.4236/jsea.2018.1110028
|View full text |Cite
|
Sign up to set email alerts
|

A Surfing Concurrence Transaction Model for Key-Value NoSQL Databases

Abstract: As more and more application systems related to big data were developed, NoSQL (Not Only SQL) database systems are becoming more and more popular. In order to add transaction features for some NoSQL database systems, many scholars have tried different techniques. Unfortunately, there is a lack of research on Redis's transaction in the existing literatures. This paper proposes a transaction model for key-value NoSQL databases including Redis to make possible allowing users to access data in the ACID (Atomicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As more and more big data-related application systems are developed, Database systems based on NoSQL are becoming increasingly popular but there are various drawbacks to NoSQL databases, like as SQL is not supported, which is an industry standard, and there are no reports or any extra capabilities, with the proposed model, the transactions of Key-Value NoSQL databases may be used in a lock-free and Multi-Version Concurrency Control free manner Li and Gu (2018). In distributed system, it is investigated that the improvement of employing cachebased query optimization to reduce response time is suitable option because it saves huge computational cost and time, especially introducing cache at each site instead of implementation of one network-based cache however, it is observed that currently cache is implemented only in homogeneous distributed databases Rana et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As more and more big data-related application systems are developed, Database systems based on NoSQL are becoming increasingly popular but there are various drawbacks to NoSQL databases, like as SQL is not supported, which is an industry standard, and there are no reports or any extra capabilities, with the proposed model, the transactions of Key-Value NoSQL databases may be used in a lock-free and Multi-Version Concurrency Control free manner Li and Gu (2018). In distributed system, it is investigated that the improvement of employing cachebased query optimization to reduce response time is suitable option because it saves huge computational cost and time, especially introducing cache at each site instead of implementation of one network-based cache however, it is observed that currently cache is implemented only in homogeneous distributed databases Rana et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transaction client, transaction manager, transaction sorter, transaction dispatcher, transaction executor, and actors are the six functional components. The waiting queue, the waiting read queue, the waiting write queue, the waiting execution queue, the executing queue, and the finished execution queue are the six queues Li and Gu (2018).…”
Section: Concurrence Transaction Modelmentioning
confidence: 99%